User Experience Analysis on the DANA Application Using the User Experience Questionnaire (UEQ) Method - Rizky Ulyani; Suhartini; Nur Aini H (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Technology has become an integral part of man's daily life by the growth and development of technology down to the present day brought many changes to mankind's survival. One of the changes to human life is the presence of a digital wallet application that can make transaction payment systems such as the application of funds easier. The study uses the User Experience Questionnaire (UEQ) method. The study aims to identify the level of user experience of applications of fund on Prabumulih university students who use apps based on variables attractiveness, variables efficiency, variables dependability, variables stimulation and novelty variables. The results of this study could be said to be positive, but in some variables it can be enhanced again.